A spectrum of pleiotropic consequences in development due to changes in a regulatory pathway. - Ana E Escalante; Sumiko Inouye; Michael Travisano (PLoS ONE, 2012)
Regulatory evolution has frequently been proposed as the primary mechanism driving morphological evolution. This is because regulatory changes may be less likely to cause deleterious pleiotropic effects than changes in protein structure, and consequently have a higher likelihood to be beneficial. We examined the potential for mutations in trans acting regulatory elements to drive phenotypic change, and the predictability of such change. We approach these questions by the study of the phenotypic scope and size of controlled alteration in the developmental network of the bacterium Myxococcus xanthus. We perturbed the expression of a key regulatory gene (fruA) by constructing independent in-frame deletions of four trans acting regulatory loci that modify its expression. While mutants retained developmental capability, the deletions caused changes in the expression of fruA and a dramatic shortening of time required for completion of development. We found phenotypic changes in the majority of traits measured, indicating pleiotropic effects of changes in regulation. The magnitude of the change for different traits was variable but the extent of differences between the mutants and parental type were consistent with changes in fruA expression. We conclude that changes in the expression of essential regulatory regions of developmental networks may simultaneously lead to modest as well as dramatic morphological changes upon which selection may subsequently act.